2011
DOI: 10.1002/cbic.201100330
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the First Bacterial Monoterpene Cyclase, a 1,8‐Cineole Synthase, that Catalyzes the Direct Conversion of Geranyl Diphosphate

Abstract: Cycling gear: A sesquiterpene cyclase (SC) homologue, CnsA, from Streptomyces clavuligerus has been identified as a monoterpene cyclase that catalyzes the conversion of GPP into 1,8‐cineole (see scheme). This suggests that bacterial SC homologues could include monoterpene cyclases, similar to plant SC homologues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 22 publications
0
48
0
4
Order By: Relevance
“…For example, cluster 3 contains pentalenene synthases, an avermitilol synthase, an acyclic terpene synthase that produces nerolidol and linalool, and a monoterpene cyclase that produces 1,8-cineole (13,14,31,32). The product diversity observed in this cluster suggests that many of the unknown terpene synthases in this cluster that are annotated as pentalenene synthases may be incorrect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cluster 3 contains pentalenene synthases, an avermitilol synthase, an acyclic terpene synthase that produces nerolidol and linalool, and a monoterpene cyclase that produces 1,8-cineole (13,14,31,32). The product diversity observed in this cluster suggests that many of the unknown terpene synthases in this cluster that are annotated as pentalenene synthases may be incorrect.…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, Hu et al reported that two other terpene synthases in this organism are involved in biosynthesis of T-muurolol and δ-cadinene (10). In the same year, Nakano et al reported the characterization of two additional terpene synthases, a monoterpene cyclase that produced 1,8-cineole and a promiscuous acyclic terpene synthase that produced linalool and nerolidol (13,14). While this manuscript was in the final stages of preparation, the function of an additional terpene synthase, which is a protein variant of the subject of this investigation, was reported to synthesize a linear triquinane of undefined stereochemistry (15).…”
mentioning
confidence: 91%
“…The terpenes that were produced by heterologous expression all accumulated in the mycelium, except for 1,8-cineole, which was generated by expression of sclav_p0982 using the vector pKU1021gps. SCLAV_p0982 has previously been shown directly by in vitro incubation to catalyze the cyclization of GPP to 1,8-cineole (47). Expression of sclav_p0982 in the heterologous Streptomyces host established that the expressed terpene synthase generates not only 1,8-cineole but also, β-pinene and camphene.…”
Section: Heterologous Expression Of Genes Encoding Bacterial Terpenementioning
confidence: 97%
“…38 This result, together with several genome mining studies for SC homologs by our group [12][13][14][15] and others, [2][3][4][5][6][7][8][9][10][11] indicates that terpenoids are significantly more widely distributed in nature than was previously appreciated, being widespread among not only eukaryotes, but also bacteria.…”
Section: Discussionmentioning
confidence: 61%
“…Recently, we reported the identification and characterization of five bacterial single-domain SC homologs: the ( þ )-caryolan-1-ol synthase GcoA 12 in Streptomyces griseus, the 1,8-cineole synthase CnsA 13 and linalool/nerolidol synthase LnsA 14 in Streptomyces clavuligerus, and the ( À)-germacradien-4-ol synthase SC1 15 and ( À)-epi-a-bisabolol synthase SC2 15 in Streptomyces citricolor. CnsA is the first bacterial monoterpene synthase known to catalyze the direct conversion of geranyl diphosphate, 13 whereas LnsA is the first bacterial acyclic terpene synthase that shows significant amino-acid sequence similarity to bacterial SCs. 14 These studies and the presence of a large number of terpene cyclase homologs in bacteria indicate that terpenoids are likely to be significantly more widely distributed in nature than previously appreciated.…”
Section: Introductionmentioning
confidence: 99%